(untitled) (Baghdad Science Journal, 2014)
The aim of this study to conduct the effects of fimbrial and lipopolysacchride (LPS) immunization is on the pathohistological changes in rabbits, Fifteen rabbits of both sexes (Weight 1500-2000 gm) divided into three groups (5 animals of each group). The first group was immunized by 1ml (200µg /animal) of fimbrial subcutaneously the second group gave 1 ml ( 200 µg /animal) LPS while the third group was left as negative control group that injected 1 ml phosphate buffer control subcutaneously. First and second groups recived the same dose after two weeks give as booster dose. All animals challenged after 5 weeks of immunization by5X107CFU/ml Proteus vulgaris intra peritoneally .After 7 days from challenge all the animals, sacrificed for histopathological examination . The results showed that the fimbrial group had a severe infiltrations of mononucleart cells in liver and kidney ,but there was no clear histopathological changes observed in the spleen compared with lipopolysaccharide and control group . Also this group showed a slight mononuclear cells infiltration in lamina properia of intestine ;while the lipopolysaccharide group showed hypertrophy of epithelial cells with a mild mononuclear cells infiltration in lamina properia as compared with the control group that showed presence of mononuclear cells aggregation in the lamina properia .Our conclusion That the defense of animals against Proteus vulgaris more efficient in fimbrial antigen than lipopolysaccharide antigen by decrease the pathological effects of this bacteria.